Misreading Michael Jensen: The Case of Nicholas Lemann's Transaction Man: The Rise of the Deal and the Decline of the American Dream. Issue 3 (22nd November 2021) - Chew, Don
Abstract : In yet another shameless exercise of editorial prerogative—the second within the past 12 months—the editor of this journal suggests that Lemann's much‐acclaimed account of 20th (and early 21st) century U.S. political economy, for all its scope and seriousness, resorts to the time‐honored practice of finding in financial markets a scapegoat for social ills that run much deeper. When examined more carefully, the U.S. market for corporate control chronicled and celebrated by Mike Jensen looks much less like the cause of economic insecurity deplored by Lemann than the only viable solution to the challenge of providing opportunities for an expanding—and increasingly global—workforce.